Early and late calls of convertible bonds: Theory and evidence - Sarkar, Sudipto (Journal of Banking & Finance, 2003)
Many convertible bonds are called too early or too late relative to the perfect markets decision rule of Ingersoll, 1977a, Ingersoll, 1977b. We re-examine the convertible call decision under corporate taxation and possible default prior to maturity. Our model predicts that early calls will be associated with high coupon and low call premium, dividend income, volatility, tax rate and interest rate; and late calls will be associated with high call premium, dividend income, tax rate and interest rate, and low coupon and volatility. These implications are supported by empirical tests carried out with five years of convertible call data.